National Crime Victimization Survey: Workplace Risk Supplement, 2002 ([Verlag nicht ermittelbar], 2014)
The primary purpose of the Workplace Risk Supplement (WRS) is to obtain accurate information regarding the incidence of violence in the workplace so that legislators and policymakers, as well as academic researchers, practitioners at the Federal, state and local levels, and special interest groups who are concerned with workplace violence, can obtain a better understanding of the risk factors associated with workplace violence.